The influence of anxiety and self-judgment on the development of eating disorders in athletes (Research, Society and Development, 2025)
Within the sports world, eating disorders are constantly observed in athletes, where this problem is extremely damaging to athletic performance and the individual's health. This study sought to analyze the influence of anxiety and self-judgment on the emergence of eating disorders in athletes, highlighting the use of restrictive nutritional behaviors and their impacts on health and athletic performance. The study consisted of a narrative literature review based on articles, consensus statements, and scientific guidelines published between 2015 and 2025 that address this problem in sports. It was evidenced that the pressure for an aesthetic ideal and self-judgment, combined with demands for better performance and external pressure, considerably increase the susceptibility of athletes to developing symptoms of anxiety and, consequently, dysfunctional eating behaviors. It was also observed that inadequate nutritional practices, as well as extremely low-calorie diets, prolonged fasting, use of medications (laxatives and diuretics), and fluid restriction, are linked to metabolic, hormonal, and psychological damage, contributing to the development and maintenance of eating disorders. On the other hand, the role of the nutritionist proved to be extremely important, as this professional is responsible for guiding the athlete within nutritional counseling using individualized approaches based on scientific evidence and integrated with psychological support, therefore fundamental for the promotion of physical and mental health and for sustainable athletic performance. It is concluded that the work of the nutritionist in the treatment of eating disorders is fundamental to the athlete's success, reiterating the need for multidisciplinary care involving various health professionals to combat this disorder.